The Role of Gut Microbiome in the Pathogenesis and Progression of Acute Pancreatitis: A Systematic Review - Miga-Orczykowska, Nadia; Sajkiewicz, Ilona; Lemieszek, Paulina; Jasiuk, Ilona; Wójtowicz, Justyna; Pustelniak, Martyna; Krukar, Katarzyna; Łukaszewska, Ewa; Rudnicka, Katarzyna; Kister, Klaudia (Journal of Education, Health and Sport, 2024)
Introduction and purpose Acute pancreatitis (AP) is one of the most common abdominal conditions leading to hospital admissions worldwide. It is characterized by an inflammatory reaction triggered by the premature activation of trypsinogen and other enzymes, resulting in pancreatic autodigestion. While most cases of AP are mild and self-limiting, approximately 15-20% of patients develop severe AP with organ failure, which is associated with a mortality rate of up to 30%. In recent years, the impact of intestinal microbiome dysregulation on various diseases has been increasingly debated. This study aims to summarize the current knowledge regarding the role of intestinal microbiota dysbiosis in the pathogenesis and progression of acute pancreatitis. Material and methods This review is based on materials collected from the PubMed database. We conducted a search using the following keywords: "acute pancreatitis," "microbiome," and "dysbiosis," focusing on articles published between 2018 and 2024. Results Studies have demonstrated a relationship between gut dysbiosis and various disorders, including digestive, metabolic, and even cancer-related conditions. It is well-established that the pancreas is closely connected to the intestines, and its exocrine function can influence the composition of the gut microbiome. This interaction is often referred to as the “gut–pancreas axis.” Conclusion The interaction between the pancreas and intestinal microbiota is believed to play a role in the pathophysiology of acute pancreatitis. Further research into this relationship could lead to the development of new diagnostic and therapeutic strategies.